Czy prekariat ma płeć? Sytuacja kobiet i mężczyzn na rynku pracy w Polsce = Does precariat have gender? Situation of women and men on labour market in Poland - Warat, Marta; Krzaklewska, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents analysis of precarious employment of women and men in Poland. The authors discuss, basing on the results of surveys carried out in 2015 among representative random sample of Poles within the project "Gender equality and the quality of life - the importance of gender equality in the development of Europe, as illustrated by the case of Poland and Norway" (GEQ), the impact the forms of employment have on the sense of stability and working and non-working balance.
Keywords: prekariat; płeć; poziom życia; rynek pracy; precariat; gender; stable standard of living; working and non-working balance; labour market